PENGEMBANGAN MEDIA PEMBELAJARAN VARIATIF DENGAN PEMANFAATAN APLIKASI CANVA PADA TINGKAT SEKOLAH DASAR - Ria Fitriani; Friska Ria Sitorus; Salim -; Putri Khairani (Bahasa Indonesia Prima, 2024)
The development of digital technology is closely related to developments in the world of education. This is because the rapid development of technology is very influential in the development of information and communication, so this provides positive benefits that can be utilized in the world of education. To produce effective learning, varied learning media are needed. This article's development of varied learning utilizes the Canva application at the elementary school level. Canva is one of the many applications that can be used to design varied learning media. As a facilitator in the learning process, the teacher's job is to present meaningful and enjoyable learning so that it can make students become more focused and arouse their thinking in order to encourage students to be motivated to learn to become students who have superior human resources and have the profile of Pancasila students.